Lockerungen und offener Vollzug Verfassungsrechtliche Grundlagen und vollzugsrechtliche Umsetzung - Arnold, Marc (Universitätsverlag Göttingen, 2020)
Temporary releases from prison and open prisons are elementary components of a rehabilitation-oriented prison system. This statement has remained unchanged after the federalism reform, with which the legislative competence for the prison system was transferred from the federal government to the states. The reform provides an opportunity to compare the 16 new state laws with each other and to examine the legal regulations on temporary releases from prisons and open prisons from admission to the penal institution through to discharge, taking into account normative administrative practice. In doing so, this is explored whether the federal states have maintained the standard established by the Federal German Prison Act of 1976, legitimized restorative tendencies or established innovations. The present work also makes a contribution to a constitutionally determined understanding of temporary releases from prison and open prisons.